Pengembangan Mesin Penggerak Ayakan Serbuk Sisa Powder Coating dengan Metode Vibrasi - Supriadi, Ari (Universitas Nusa Putra, 2020)
Sarandi Karya Nugraha is a company engaged in the manufacture of medical devices which almost 85% of its products use paint from powder coating, so many powder coatings are wasted and used as powder coatings. However, the former powder coating can still be used as a mixture with a new powder coating. The ratio between used powder coating and new powder coating is 1: 3. During this time at PT. Sarandi Karya Nugraha filtering powder coating is done manually. This does not guarantee the quality of the powder coating so that it can affect the quality of the product produced. Therefore, a tool is made in the form of a powder coating vibrator filter that functions to maintain the quality of thepowder coating and efficiency of filtering time, thereby increasing operator productivity.